EVALUATION OF MICROBIOLOGICAL CONTAMINATION PARAMETERS OF HERBAL DRINK AND INSTANT POWDER - PRATAMI, DIAH KARTIKA; MALIKHAH, TIKA; AULENA, DESI NADYA; YANTIH, NOVI; KUMALA, SHIRLY (International Journal of Applied Pharmaceutics, 2022)
Objective: The aim of this study was to determine whether the microbial contamination contained in herbal medicine in the form of herbal drink (liquid) and instant powder fulfil(s) the requirements of BPOM No. 32 of 2019. Methods: Determination of microbial contamination was carried out by testing the total plate count using TSA (Tryptic Soy Agar) media, Yeast and Mold count plates using SDA (Sabouraud Dextrose Agar) media, Escherichia coli using MCB selective media (MacConkey Broth) and MCA (MacConkey Agar), Salmonella using RVSEB (Rappaport Vassiliadis Salmonella Enrichment Broth) and XLD (Xylose Lysine Deoxycholate) media, and Shigella using XLD (Xylose Lysine) media Deoxycholate) and also MCA (MacConkey Agar). Results: The result of the herbal drink the total plate count is 1.2 x 102 CFU/g, yeast and mold count plates was<10 CFU/g, Escherichia coli was negative/g, Salmonella enterica Serovar Thypimurium was negative/g, and Shigella sonnei which was negative/g. while in instant powder samples test showed that the total plate count was<10 CFU/g, the yeast and mold count plates was<10 CFU/g, Escherichia coli was negative/g, Salmonella enterica Serovar Thypimurium was negative/g, and Shigella sonnei was negative/g. Conclusion: Based on the results of data analysis from the two samples, the herbal medicine produced as herbal medicine has fulfilled the applicable requirements